Penguatan Literasi dan Numerasi di SDN 022 Kota jambi - Wahyuni, Anny; Adi Saputra, Muhammad; Yaldi, Destri; Mareta, Yoan; Salam, M. (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
This service is motivated by the independent curriculum policy which has a program to improve literacy and numeracy of students. Strengthening literacy and numeracy for students at SDN 022 Kota Jambi requires the involvement of various stakeholders such as school supervisors, principals teachers, and teaching staff at school. The purpose of the literacy and numeracy service at SDN 022 Jambi City is first, to hone and strengthen the knowledge and numeracy skills of students in interpreting numbers, data, tables, graphs and diagrams. Second, to apply literacy and numeracy knowledge and skills to solve problems and make decisions in everyday life based on logical considerations. Third, forming and strengthening resources (SDA) to be able to compete and collaborate with other nations for the prosperity and welfare of the nation and state. The literacy and numeracy program is carried out in the form of making reading corners, literacy trees, numeracy ice, making fraction pizzas and socializing the 3 big sins of education.